Advanced medical interventions in pleural disease. (June 2016) - Bhatnagar, Rahul; Corcoran, John P.; Maldonado, Fabien; Feller-Kopman, David; Janssen, Julius; Astoul, Philippe; Rahman, Najib M.
The burden of a number of pleural diseases continues to increase internationally. Although many pleural procedures have historically been the domain of interventional radiologists or thoracic surgeons, in recent years, there has been a marked expansion in the techniques available to the pulmonologist. This has been due in part to both technological advancements and a greater recognition that pleural disease is an important subspecialty of respiratory medicine. This article summarises the important literature relating to a number of advanced pleural interventions, including medical thoracoscopy, the insertion and use of indwelling pleural catheters, pleural manometry, point-of-care thoracic ultrasound, and image-guided closed pleural biopsy. We also aim to inform the reader regarding the latest updates to more established procedures such as chemical pleurodesis, thoracentesis and the management of chest drains, drawing on contemporary data from recent randomised trials. Finally, we shall look to explore the challenges faced by those practicing pleural medicine, especially relating to training, as well as possible future directions for the use and expansion of advanced medical interventions in pleural disease. Technological advances and greater availability of techniques give a broad range of interventions for pleural disease http://ow.ly/ZNya2